Patterns in the Landscape and Erosion of Cultural Sites Along the Colorado River Corridor in Grand Canyon, USA. Issue 6 (30th September 2014) - Pederson, Joel L.; O'Brien, Gary R.
<x xml:space="preserve">Abstract</x> The geologic and geomorphic template of Grand Canyon influences patterns in the archaeological record, including sites where apparent increases in erosion may be related to Glen Canyon Dam. To provide geoarchaeological context for the Colorado River corridor and such issues, we explore first‐order trends in a database of field observations and topographic metrics from 227 cultural sites. The patterns revealed may be expected in other river‐canyon settings of management concern. The spatial clustering of sites along the river follows variations in width of the valley bottom and the occurrence of alluvial terraces and debris fans, linking to bedrock controls. In contrast, the pattern of more Formative (Ancestral Puebloan, 800–1250 A.D.) sites in eastern Grand Canyon and Protohistoric (1250–1776 A.D.) sites in western Grand Canyon does not follow any evident geomorphic trends. In terms of site stability, wider reaches with more terrace and debris fan landforms host a disproportionate number of sites with acute erosion. This links most directly to weak alluvial substrates, and the primary erosion process is gullying with diffusive‐creep processes also pervasive. Although Glen Canyon Dam does not directly influence these erosion processes, overall sediment depletion and the loss of major flooding leaves erosion unhampered along the river corridor.